Urgensi Pengaturan Cyber Insurance (Asuransi Siber) Wajib Bagi Bank - Fitrianto, Bambang; Armayanti, Rika; Siagian, Sahat (Sharia Journal and Education Center Publishing, 2025)
The rapid development of information technology and the digitalization of banking services have brought convenience as well as new risks in the form of increasingly complex cyber threats, such as data breaches, system hacking, and operational disruptions. These cyber risks not only affect the internal stability of banks but also potentially cause losses to customers and undermine public trust in the national financial system. Although the Indonesian banking regulatory framework has addressed risk management and data protection, specific regulations concerning mandatory cyber insurance for banks have not yet been comprehensively established. This study aims to analyze the urgency of regulating cyber insurance as a legal obligation for banks in order to strengthen legal protection, risk mitigation, and banking system stability. The research employs a normative legal method with statutory and conceptual approaches by examining banking regulations, data protection laws, and legal doctrines related to risk management and insurance. The findings indicate that cyber insurance plays a strategic role as a non-financial risk mitigation instrument by providing financial protection against losses caused by cyber attacks. Therefore, the mandatory regulation of cyber insurance for banks is an urgent necessity to ensure customer protection, enhance banking resilience, and support trust and stability within the national financial system.